2017
DOI: 10.1093/gerona/glx068
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Co-Occurrence of Geriatric Syndromes in People Aged 75 Years and Older in France: Results From the Bordeaux Three-city Study

Abstract: GSs were very common in this French elderly population and were grouped into two major dimensions: the "Dementia-Dependence-Incontinence" and "Frailty-Depression-Isolation."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 34 publications
5
46
1
1
Order By: Relevance
“…However, at this follow-up, the representativeness of our population sample has been compared with the database of INSEE for Bordeaux area population and there was no significant difference in age, sex distribution, residency location, and loneliness index. 46 Furthermore, demographic characteristics were not significantly different between included and nonincluded participants of the study (Table 1) and the prevalence of glaucoma we found was similar to those observed in other studies. [67][68][69] Hence, our findings need to be replicated in another population sample to confirm all these associations.…”
Section: Skin Autofluorescence As a Risksupporting
confidence: 88%
See 1 more Smart Citation
“…However, at this follow-up, the representativeness of our population sample has been compared with the database of INSEE for Bordeaux area population and there was no significant difference in age, sex distribution, residency location, and loneliness index. 46 Furthermore, demographic characteristics were not significantly different between included and nonincluded participants of the study (Table 1) and the prevalence of glaucoma we found was similar to those observed in other studies. [67][68][69] Hence, our findings need to be replicated in another population sample to confirm all these associations.…”
Section: Skin Autofluorescence As a Risksupporting
confidence: 88%
“…There was no significant difference in age or sex distribution, residency location, and loneliness index between our population sample and data of Bordeaux area population. 46 This research was approved by the Ethical committee of Bordeaux (Comité de Protection des Personnes Sud-Ouest et Outre-Mer III) in May 2006 and followed the declaration of Helsinki's tenets. All participants provided informed written consent for enrollment in the study.…”
Section: Study Populationmentioning
confidence: 99%
“…Furthermore, ARIC includes a more racially diverse population than these other analyses. 47,48 Our study details a clear association between HF and MCI as well as dementia, which is less well described in current literature.…”
Section: Discussionmentioning
confidence: 63%
“…old age, cognitive impairment, functional impairment and immobilization), they frequently co‐occur, and one geriatric syndrome might even cause more geriatric syndromes . Furthermore, geriatric syndromes tend to co‐occur in a single patient . For example, Bells et al reported that 55% of patients who were transferred to healthcare facilities had three or more geriatric syndromes, and Tabue‐Teguo et al described interactions between 10 co‐occurring geriatric syndromes using multiple correspondence analysis .…”
Section: Discussionmentioning
confidence: 99%